Selecting effective treatments : a comprehensive, systematic guide to treating mental disorders - Seligman, Linda; Reichenberg, Lourie W. , 1956- (John Wiley & Sons, 2012)
A direct and personalized approach to helping practitioners and students understand the diagnostic criteria from the DSM-IV-TR, this book organizes the relevant current literature in the treatment of the major mental disorders into a carefully structured format that helps clinicians quickly assess the client and develop successful treatment plans